Feasibility Study of Contrast‐Enhanced Automated Acoustic Mammography. (1st May 2013) - Gaitini, Diana; Rothstein, Tamara; Gallimidi, Zahava; Azhari, Haim
Abstract : The feasibility of implementing image subtraction in through‐transmission breast sonography was examined. Acoustic mammograms of women with suspicious findings were obtained using through‐transmission imaging. Precontrast images were initially acquired. Then a perflutren liquid microsphere contrast agent solution was injected intravenously, and new sets of images were acquired. Precontrast‐postcontrast subtraction images depicting the resulting changes were then obtained and visually compared with other imaging modalities. The ability to detect changes stemming from contrast agent injection in the through‐transmission mode was verified. The comparability with x‐ray mammography and magnetic resonance imaging was shown. Finally, the ability to compare images obtained before and several months after surgery was confirmed.